The relationship between arm muscle strength, muscle endurance, balance and draw force length on archery performance / Maisarah Mohd Saleh ... [et al.] - Mohd Saleh, Maisarah; Linoby, Adam; Abdul Razak, Fatin Aqilah; Abu Kasim, Nurul Ain; Mohamed Kassim, Nur Atikah (Universiti Teknologi MARA, 2022)
Archery is a type of sport which participants release the arrow after aiming the target. The shot of an arrow must be accurate to the highest score on the target face. Purpose: The purpose of this study was to determine the most the most contributing variable in archery performance. Methodology: A total of 31 females and males, aged between 13 - 18 years old from Pusat Latihan Negeri Unit Sukan Prestasi Tinggi, Majlis Sukan Negeri, Negeri Sembilan participated in this study. They were involved in different level of achievement in archery competition, ranging from beginner until expert archers. They were also free from any injuries. The participants engaged in three tests, which were arm muscle strength test, push-up test, stork balance stand test. Result: The Pearson correlation analysis showed there was significant relationship among variable measured. In addition, regression analysis showed the arm muscle strength and muscle endurance were the most contributed variable in archery performance. Findings and discussion: These elements can be indicators of an archer's skill level and can be applied as important parameter to select potential archers and also assessment of archer's performance. The time taken to develop the archer to become an expert archer can be shortening due to focusing on important variables.